Design and analysis of a multi-configuration wheel-leg hybrid drive robot machine. (13th April 2023) - Hou, Feng; Yuan, Jiwei; Li, Kunpeng; Wang, Zhouyi
The use of robots to perform tasks in extreme environments instead of humans has gradually become important. For wider applications, robots should be able to adapt to complex environments, such as typical height/width-restricted motion spaces, raised obstacles, and ravines. The structure is the foundation of robot to move and perform tasks. In this study, a variable-attitude robot mechanism is designed and analyzed. With the link leg drive and Mecanum wheel drive, the robot has various configurations and omnidirectional motion capabilities. First, the design and analysis of the wheel drive system are performed, and the mapping relationship between the velocity of the robot and the velocity of the Mecanum wheel is clarified. Second, kinematics of the linkage drive system is analyzed, including the motion space, trajectory characteristics, and the effect of variable axle spacing on the robot motion performance. Subsequently, a simulation is used to verify the rationality of the three motion modes of the robot: walking, wheel drive, and hybrid drive. Finally, a motion simulation of several typical configuration changes in the robot is observed, and the feasibility of the robot mechanism to adapt to a complex environment is verified. This study contributes to the development and application of special advanced robots.